The impact of high-speed trains on the service life of rails (Международный научный журнал «Инженер», 2026)
This article examines the defects occurring in rails used on the high-speed sections of UzbekistanRailways. Additionally, the impact of train movements on the rails is considered. The article mainlyfocuses on rails and the frequently occurring defects in them. Since rails hold a special place, greatattention is paid to the development of technologies that assess all problems related to rails and themetallurgical industry, as well as the defects and damages that serve as the basis for evaluating railconditions. The article also considers the high-speed section of the Tashkent - Samarkand railway line asthe main object of study.